Shade tolerance in Swarnaprabha rice is associated with higher rate of panicle emergence and positively regulated by genes of ethylene and cytokinin pathway - Panigrahy, Madhusmita (Sci Rep, 2019)
This study identifies characteristics of seedling, mature plant phenotypes, changes at genetic and genomic level associated with Swarnaprabha (SP) rice grown under prolonged shade and compared with Nagina 22 (N22). Coleoptile length under low red/far-red was intermediate between that in dark and red light in a 7-days growth frame. Whereas, highest rootlet number was discriminating in seedlings grown for 28 days in hydroponics. In shade, SP and N22 both showed several tolerant mature plant phenotypes, except the panicle length, yield per plant and % grain filling, which were higher in SP. Percentage decrease in yield / plant in shade showed significant positive correlation with increase in NDVI, decrease in panicle length and % grain filling (p ≤ 0.01). Rate of panicle emergence in shade was higher in SP than N22. Expression patterns of PHYTOCHROME INTERACTING FACTOR LIKE-13 and PHYTOCHROME B were contrasting in SP and N22 seedlings under continuous red or red/far-red. Microarray analysis revealed the up-regulation of most of the ethylene and cytokinin pathway genes in shade grown panicles of SP. Significant up-regulation of ETHYLENE RESPONSE ELEMENT BINDING PROTEIN-2, MOTHER OF FLOWERING TIME 1, and SHORT PANICLE1 genes in shade grown panicles of SP could explain its sustainable higher yield in shade.